Suicide in prisoners with bipolar disorder and other psychiatric disorders: a systematic review. - Fazel, S; Wolf, A; Geddes, J (2013)
OBJECTIVES: To examine the risk of suicide and suicide attempts in prisoners with bipolar disorder and other psychiatric disorders compared with prisoners without psychiatric disorders. METHODS: We conducted a systematic review and meta-analysis of observational studies comparing suicide outcomes in prisoners with bipolar disorder and other psychiatric disorders to other prisoners. RESULTS: Five studies reported the risk of suicidal outcomes in prisoners with bipolar disorder compared with other prisoners, with a random effects pooled odds ratio of 2.4 (95% confidence interval: 1.6-3.7; I(2) = 0%). This appeared to be lower than the risk of suicidal outcomes for all psychiatric disorders and for depression, specifically, and, in meta-regression, significantly lower (p = 0.03) than for schizophrenia-spectrum disorders. CONCLUSIONS: Although bipolar disorder is associated with suicide and non-fatal suicidal behavior in prisoners, further research is necessary to confirm any associations and mediating mechanisms.